Prevalence, incidence, and risk factors of intestinal parasites in Danish primary care patients with irritable bowel syndrome. (March 2014) - Engsbro, Anne Line; Stensvold, Christen Rune; Nielsen, Henrik Vedel; Bytzer, Peter
Abstract The gut microbiota may be involved in the aetiopathogenesis of irritable bowel syndrome (IBS). We studied the role of intestinal parasites by describing the epidemiology and risk factors for infection in primary care patients aged 18–50 y with IBS. One hundred and thirty-eight patients at baseline and 78/116 patients returning 1 y later, submitted faecal samples that were examined by microscopy, culture for Blastocystis, and real-time PCR for Dientamoeba fragilis, Entamoeba (dispar and histolytica), Cryptosporidium spp., and Giardia intestinalis. Overall, 42–45% of patients harboured intestinal parasites (baseline and follow-up, respectively): D. fragilis carriage was 35–41%; Blastocystis 14–20%. Incidence rates for D. fragilis and Blastocystis were 10 and 4 per 100 person-y, respectively. Blastocystis carriage increased the odds for carrying D. fragilis. Clinical comparisons showed D. fragilis to be associated with a low frequency of defecation. Further, D. fragilis was associated with having children aged 5–18 y and Blastocystis with increasing age.